Gene Frequency and Heritability of Rh Blood Group Gene in 44 Human Populations - Supriyo CHAKRABORTY (Notulae Scientia Biologicae, 2010)
The frequency of RhD and Rhd alleles of Rh blood group gene was estimated in 44 human populations distributed all over the world from the RhD phenotypic data. The average frequency of RhD and Rhd allele over these populations was 0.70 and 0.30, respectively. Higher frequency of RhD allele than the expected estimate (0.50) in all the populations, under Hardy-Weinberg equilibrium condition assuming equal frequency of both alleles in the initial population, indicated inbreeding at RhD/d locus as well as natural selection for RhD allele. Very high heritability estimate (84.04%) of Rh allele frequency revealed that this trait was under weak selection pressure and resulted in greater genetic variation in existing populations. It is consistent with Fishers fundamental theorem of natural selection. The results from the present study suggest that inbreeding at RhD/d locus and some other factors (possibly mutation, migration and genetic drift) other than natural selection alone played major roles in changing the Rh allele frequency in these populations.